The effect of temperature on microbial growth in apple cubes packed in film and preserved by use of orange juice - Andres, Silvina Cecilia (2004)
Red delicious apple cubes were packed in fresh orange juice containing chemical preservatives (citric and ascorbic acid, potassium sorbate) and covered with plastic films of different gas permeabilities (polyethylene and EVA-SARAN-EVA) before storage at 4, 10 and 20°C. The concentration of potassium sorbate in the product was optimized with respect to colour and microbial growth. Yeast and mould growth was modelled by Gompertz and linear equations to derive parameters such as lag phase, maximum microbial population and specific microbial growth or rates of decline. Activation energies for the specific growth rates were estimated from Arrhenius-type equations and the time required to reach microbial counts of 106±0.2 CFU g -1 was determined in all cases. At 4°C, these values were longer than 25 days in all systems tested. The use of a low gas permeability film and an adequate potassium sorbate concentration extended storage life at higher temperatures.